Strategi Penetapan Harga dan Kualitas Layanan Terhadap Loyalitas Konsumen Fitness Center Khusus Wanita - Aulia Nur Fadila; Halimah Zahrah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The growing awareness of healthy lifestyles among women has encouraged the development of women-only fitness centers that emphasize comfort and privacy. In an increasingly competitive fitness industry, pricing strategies and service quality play a crucial role in building consumer loyalty. This study aims to analyze the influence of pricing strategy and service quality on consumer loyalty at Akhwat Gym Bandung. The research employs a quantitative approach with a causal design using a survey method involving registered members. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that pricing strategy and service quality have a positive effect on consumer loyalty, with service quality showing a more dominant influence. These findings suggest that fair pricing aligned with perceived value and professional, customer-oriented service can enhance consumer loyalty. This study concludes that appropriate pricing management and continuous improvement of service quality are key factors in maintaining long-term loyalty in women-only fitness centers